IUS press and information activities (International Union of Students, 1986)
Image of the globe, surrounded by logos of various publishing organisations of the IUS; logo of the 40th anniversary of the IUS on top right Poster commemorating 40 years of the International Union of Students, 1987, and advertising its publications PO-1708